Enzyme-Linked Immunosorbent Spot Assay Analysis of Peripheral Blood Lymphocyte Reactivity to Donor HLA-DR Peptides - Nader Najafian; Alan D. Salama; Eugenia V. Fedoseyeva; Gilles Bénichou; Mohamed H. Sayegh (2002)
ABSTRACT. Chronic allograft dysfunction, which is the most common cause of late allograft failure, is in part caused by an ongoing immune response orchestrated by T lymphocytes primed by the indirect pathway of allorecognition. The low frequencies of such T cells have made it difficult to study indirect alloreactivity by using currently available assays. The development of a sensitive, clinically useful method of measuring indirect alloreactivity among human renal transplant recipients was thus attempted. Furthermore, in a pilot immunologic study, the contribution of the indirect pathway was studied in two groups of renal transplant recipients, i.e., patients with no prior acute rejection episodes and stable renal function ("stable" patients) and patients with at least one previous episode of biopsy-proven acute rejection, who were thus at risk for the development of chronic rejection ("high-risk" patients). The frequencies of type 1 T helper (interferon-γ-producing) and type 2 T helper (interleukin-5- and -10-producing) peripheral blood lymphocytes reactive with a panel of synthetic peptides (corresponding to sequences from donor HLA-DR molecules) were determined for renal transplant recipients and normal control subjects by using an enzyme-linked immunosorbent spot assay (ELISPOT). Among recipients of DR-mismatched allografts, a cut-off value of 60 interferon-γ spots/106 cells significantly (P = 0.02) separated stable patients (creatinine concentration, 1.1 ± 0.3 mg/dl) from high-risk patients (creatinine concentration, 2.3 ± 1.7 mg/dl). This is the first demonstration that the enzyme-linked immunosorbent spot assay can be used to monitor indirect alloreactivity to donor HLA-DR peptides among renal transplant recipients. These data provide the rationale for the prospective study of indirect alloreactivity among transplant recipients, to allow predictions of which patients would be at risk for the development of chronic rejection and thus allow appropriate planning of future interventions.